(untitled) (Global Journal of Management and Business Research, 2018)
Agriculture is major source of employment and food to our country but even this sector is facing various problems from many years. The problem of availability of credit is one of them, due to this problem the agricultural production get affected every year. The Present Study focuses over the fund disbursement to agricultural sector by NABARD in Uttar Pradesh. The Present Study indicates the preferences of NABARD in financial assistance to different sectors including agriculture sector. The present paper is an attempt by the researchers to examine the role of NABARD in agriculture in Uttar Pradesh through financial disbursements made by it directly. The study is purely based on secondary data which were analyzed with the help of mean, percentage, CAGR, one-way ANNOVA, Post Hoc Test, Tukey etc. to draw the results. The study also exhibited that NABARD continuously focuses on NFS, and farm mechanization, however, agriculture which assumes great significance in present day scenario, is yet to get its dues from Bank. It was established through the study that there is a significant difference in refinance disbursement of NABARD through Purpose and Programme-wise to various sectors.